(Penilaian awal perubatan sel salur kayu Baeckea frutescens yang dipengaruhi oleh impak akibat aktiviti rekreasi di Gunung Tahan, Malaysia)Preliminary assessments on the changes in wood vessel characteristics of Baeckea frutescens influenced by the impacts of recreational activities at Mount Tahan, Malaysia - Azita Ahmad Zawawi,; Masami Shiba,; Hazandy Abdul Hamid,; Mohd Zaki Hamzah,; Pakhriazad Hassan Zaki, (Universiti Kebangsaan Malaysia, 2012)
Vessel arrangement of Baeckea frutescens were studied to determine its anatomical differences as impacted by recreational activities at Gunung Tahan, Malaysia. Plots sized 20 m × 20 m represent disturbed and control areas were established in the most visited camping sites. The study demonstrated that there were differences of vessel arrangements in B. frutescens selected among the study areas. Our result showed that B. frutescens grew in the disturbed plot had higher vessel areas compared with the control plot with the mean values of 177.06 μm2 and 106.40μm2, respectively. For growth attributes, the average tree diameters in all the test sites were 2.10 and 1.55 cm at disturbed plot and control plot, respectively while the tree heights varied from 0.95±0.04 to 0.82 ±0.06 m for the disturbed and the control plots, respectively. Most previous studies indicated that wood anatomical characteristics are genetically fixed by species. However, interestingly, it was found from this study that vessel arrangement which is genetically influenced can change as a response to interferences and disturbances, depending on the ecological conditions.